Metabolic Syndrome and Dementia risk in a Multiethnic Elderly Cohort - Muller, Majon (2007)
BACKGROUND/AIMS: The metabolic syndrome (MeSy) may be related toAlzheimer’s disease (AD). Our aims were to investigate the association of the MeSy with incident dementia in a multiethnic elderly cohort in the United States. METHODS: We conducted Cross-sectional and prospective analyses in 2,476 men and women aged 65 years and older and with data available on the metabolic syndrome and dementia diagnosis in Northern New York City. MeSy was defined by the NCEP-ATPIII and EGIR-criteria. Dementia was diagnosed using standard criteria. RESULTS: No association was found between MeSy and prevalent dementia. After 4.4 years of follow-up, 236 individuals of the 1,833 without prevalent dementia, developed dementia. MeSy was not associated with incident dementia. Of the components of the MeSy, diabetes and hyperinsulinemia were associated with an increased incident AD (HR; 95%CI respectively 1.4; 1.0–2.1 and 1.4; 0.9–2.7) and DAS risk(HR; 95%CI respectively 1.9; 1.1–3.1 and 2.3; 1.1–4.7). CONCLUSIONS: The MeSy was not associated with an increased dementia risk in a multiethnic elderly cohort, but diabetes and hyperinsulinemia were. In the elderly, examining diabetes and hyperinsulinemia separately may be preferable to using the MeSy as a risk factor.